Diseño e implementación de algoritmo de predicción en base al muestreo de datos de una red de sensores para la Empresa Rosaprima - Díaz Quishpe, Luis Fernando (2018)
Today Business Intelligence techniques are a great tool within enterprises because they have allowed them to take advantage of all their technological resources at the maximum of its capacities. Above all, the internal and external information that a business generates every second have an important role in the decision making of the company. Data mining, a useful tool within BI, has allowed information to become the most important asset of the companies. It takes data saved in storages and using arithmetic algorithms analyzes the behavior of data, searching for repetitive patterns that will make easier the decision making process. It also brings the possibility of showing statistics of sales, productivity and even better areas of improvement within company. In this project, it well demonstrates how data obtained from different databases can be represented in one algorithm which once it applied could give a prediction as the output.